Antifungal use via outpatient parenteral antimicrobial therapy. Issue 10 (16th August 2022) - Chew, Su M.; Heath, Christopher H.; Petursson, Cecilia; Boan, Peter A.; Robinson, James Owen; Italiano, Claire M.; Dyer, John R.; Manning, Laurens; Ingram, Paul R.
Abstract: Background: Antifungal administration via outpatient parenteral antimicrobial therapy (OPAT) is infrequent. As patients with invasive fungal infections (IFIs) receiving OPAT are at high risk of readmissions, careful, risk‐based patient selection and monitoring is important. Objectives: To describe our experience managing IFIs via OPAT, including assessment of risk factors associated with unplanned readmissions. Patients and Methods: A retrospective cohort study of outpatients from two tertiary hospitals in Western Australia managed with parenteral antifungals for the treatment of IFIs from 2012 to 2020. Outcomes assessed were unplanned OPAT‐related readmissions; adverse events and achievement of treatment aim at the completion of OPAT. Results: Forty‐six patients were included, encompassing 696 OPAT days. Twenty‐three (50%) patients received intravenous (IV) liposomal amphotericin B (L‐AmB), 23 (50%) received IV echinocandins and one (2%) patient received IV fluconazole. One patient received both IV L‐AmB and an echinocandin. Unplanned OPAT‐related readmissions occurred in 13 (28%) patients and any adverse event occurred in 19 (41%), most commonly nephrotoxicity amongst patients receiving L‐AmB. On univariate analysis, unplanned OPAT‐related readmissions were more common in Mucorales infection, L‐AmB doses of ≥5 mg/kg and otorhinolaryngologic (ENT) infections. At the completion of OPAT, attainment of treatment aims occurred in 28 (61%) patients. Conclusions: Patients receiving parenteral antifungals via OPAT experience high rates of unplanned readmissions and adverse events. Risk factor identification may facilitate optimal patient selection and establishment of treatment aims.